ACUTE EFFECT OF RED PITAYA JUICE SUPPLEMENTATION ON RUNNING PERFORMANCE AND MUSCLE DAMAGE AMONG CADETS - Siti Maizura Mohd Daud (Tesis, 2022)
This study investigated the acute effect of red pitaya juice (DRG) supplementation on running time-trial (TT) performance and muscle damage after a high-intensity exercise among cadets.